Myeloid LXR (Liver X Receptor) Deficiency Induces Inflammatory Gene Expression in Foamy Macrophages and Accelerates Atherosclerosis. Issue 6 (28th April 2022) - Endo-Umeda, Kaori; Kim, Eunyoung; Thomas, David G.; Liu, Wenli; Dou, Huijuan; Yalcinkaya, Mustafa; Abramowicz, Sandra; Xiao, Tong; Antonson, Per; Gustafsson, Jan-Åke; Makishima, Makoto; Reilly, Muredach P.; et al.
Abstract : Background: Cholesterol loaded macrophage foam cells are a prominent feature of atherosclerotic plaques. Single-cell RNA sequencing has identified foam cells as TREM2 (triggering receptor expressed on myeloid cells 2) positive populations with low expression of inflammatory genes, resembling the TREM2 positive microglia of neurodegenerative diseases. Cholesterol loading of macrophages in vitro results in activation of LXR (liver X receptor) transcription factors and suppression of inflammatory genes. Methods: To test the hypothesis that LXRs mediate anti-inflammatory effects in Trem2 expressing atherosclerotic plaque foam cells, we performed RNA profiling on plaque cells from hypercholesterolemic mice with myeloid LXR deficiency. Results: Myeloid LXR deficiency led to a dramatic increase in atherosclerosis with increased monocyte entry, foam cell formation, and plaque inflammation. Bulk cell-RNA profiling of plaque myeloid cells showed prominent upregulation of inflammatory mediators including oxidative, chemokine, and chemotactic genes. Single-cell RNA sequencing revealed increased numbers of foamy TREM2-expressing macrophages; however, these cells had reduced expression of the Trem2 gene expression module, including phagocytic and cholesterol efflux genes, and had switched to a proinflammatory and proliferative phenotype. Expression of Trem2 was suppressed by inflammatory signals but not directly affected by LXR activation in bone marrow-derived macrophages. Conclusions: Our current studies reveal the key role of macrophage LXRs in promoting the Trem2 gene expression program and in suppressing inflammation in foam cells of atherosclerotic plaques.